Does Goal-Demotion Enhance Cooperation? - Mitkidis, Panagiotis (Journal of cognition and culture, 2014)
Social scientists have long assumed that religion – and more specifically religious rituals – promotes cooperation. It has also been claimed that ritual plays an essential role in enhancing prosociality and cooperation. In this study, using a controlled laboratory experiment, we investigate if a conspicuous and recurrent feature of collective ritualized behaviour, goal-demotion, promotes lasting cooperation. We report that goal-directed collective behaviour is more efficient than goal-demoted behaviour for motivating participants to engage in ulterior cooperation. Plausible interpretations of the data and of the mechanisms involved are discussed.